Clinical study of a multivitamin and polymineral complex associated with Panax ginseng extract (Natus Gerin®) - Perazzo, Fabio F.; Souza, Gustavo H.B.; Maistro, Edson Luis [UNESP]; Rodrigues, Marcelo; Fonseca, Fernando L.A.; Carvalho, Jose C.T. (My University, 2011)
This study aimed to stablish the efficacy of a multivitamin and polyminerals supplemented with Panax ginseng extract (Natus Gerin ®) on patients subjected to common physical or mental stress. Patients were randomly divided in two groups and underwent a thorough clinical examination. Group A received Natus Gerin ® capsules and B placebo capsules. Two capsules were taken daily during meals during four weeks. Mood and physical activity were evaluated through a questionnaire assessing quality of life. From the 176 patients enrolled, 17 were excluded due to voluntary withdrawal, 81 completed the study in group A and 78 in group B. The treatment with Natus Gerin ® increased the quality of life when compared to placebo. After 15 and 30 days, group A showed a significant increase in average scoring score from 1.78 to 3.78, and finally 5.32 points. The study has shown that the daily use of Natus Gerin ® can be effective in improving quality of life in patients suffering from physical and mental stress.
Keywords: Mineral; Mood; Panax ginseng; Sexual activity; Vitamin; ginseng extract; ginseng extract plus multivitamin; multivitamin; natus gerin; placebo; unclassified drug; adult; aged; clinical examination; clinical study; controlled study; double blind procedure; drug efficacy; female; headache; human; influenza; libido; major clinical study; male; mental stress; mood; nausea; physical activity; physical stress; quality of life; questionnaire; randomized controlled trial; scoring system; side effect; stomach irritation